Penerapan Prinsip Bagi Hasil Akad Mudharabah Di Perbankan Syariah Dalam Pandangan Ekonomi Di Indonesia - Ridha, Fahrul (Yayasan Rahmat Islamiyah, 2023)
Sharia banking is now undergoing a rapid development in Indonesia. It just means that in its implementation half of the group is thinking that sharia banks are only in line with the identity that is used to maintain solidarity with Muslim groups in the banking sector. Mudharabah contracts form one of the products used in sharia banking. This research aims to understand the explanation regarding the implementation of the profit sharing principle in mudharabah contracts in sharia banking from an economic perspective. In a mudharabah investment profit sharing transaction, both parties can create a business agreement, where one party represents the capital participant and the other party represents the capital manager. From the management of investment funds, you will receive investment profits (profit) and will then be divided into two according to agreement (al-ittifaq). This research uses a qualitative approach based on literature study. Profit sharing, for example in mudharabah and musyarakah contracts, must have existed before Islam. In non-Islamic Eastern circles, the business class is based on the principle of mudharabah, moving closely to the rules of interest method loans so that the system will help various economic activities and intensify sharia social finance, for example zakat, infaq, alms and waqf. On the other hand, after the arrival of Islam, financial businesses based on interest were banned and all funds had to be channeled to principal profits.